Wojciech Żukrowski (who We do not Remember) – for the Young Reader - Wzorek, Anna (Respectus Philologicus, 2014)
The main objective of the article is to discuss the forgotten works of Wojciech Żukrowski written for young people. The author is remembered by young readers as the one who created the fairy places of Tiutiurlistan and Blabancja (from the novels of Porwanie w Tiutiurlistanie [Kidnapping in Tiutiurlistan] and Na tronie w Blabonie [On the Throne in Blabon] and collected Vietnamese legends (Ognisko w dżungli [Fire in the Jungle]). However, Żukrowski wrote numerous texts addressed to children and young people which did not gain so much popularity, such as two modern novels of Słoneczne lato [Sunny Summer] (1952) and Poszukiwacze skarbów [Treasure Hunters] (1954), a “Vientamese” short story Mój przyjaciel słoń [My Friend the Elephant] (1957) as well as historical novels Szabla Gabrysia [Sabre Gabriela] (1952) and a short poem Bal w agreście [The Ball in a Goosberry Field] (1943). The article analyses the present titles and poses a very important question concerning the causes of the works being so unsuccessful. It is stated in the summary of the article that the forgotten works by Żukrowski written for young people are not devoid of values and comprise numerous aesthetic qualities (Bal w agreście), cognitive values (Poszukiwacze skarbów, Mój przyjaciel słoń) or educational values (Słoneczne lato or Mój przyjaciel słoń). The works by Wojciech Żukrowski analysed in the article are, however, anachronistic for a modern reader and outdated mainly due to the subject matter they tackle as well as included socrealistic elements.
Keywords: literature for children and young people; Wojciech Żukrowski; social realism